Effects of glucose oxidase on growth performance, clinical symptoms, serum parameters, and intestinal health in piglets challenged by enterotoxigenic Escherichia coli - Wang, Weiwei; Xie, Ruiyan; Cao, Qingyun; Ye, Hui; Zhang, Changming; Dong, Zemin; Feng, Dingyuan; Zuo, Jianjun (Frontiers in Microbiology, 2022)
Glucose oxidase (GOD) could benefit intestinal health and growth performance in animals. However, it is unknown whether GOD can protect piglets against bacterial challenge. This study aimed to evaluate the protective effects of GOD on growth performance, clinical symptoms, serum parameters and intestinal health in piglets challenged by enterotoxigenic Escherichia coli (ETEC). A total of 44 male weaned piglets around thirty-eight days old were divided into 4 groups (11 replicates/group): negative control (NC), positive control (PC), CS group (PC piglets + 40 g/t colistin sulfate) and GOD group (PC piglets + 200 g/t GOD). All piglets except those in NC were challenged with ETEC (E. coli K88) at 11 d of the experiment. Parameter analysis was performed at 21 d of the experiment. The results showed that ETEC challenge elevated (P < 0.05) the rectal temperature and fecal score of piglets at certain time-points post challenge, reduced (P < 0.05) serum glucose and IgG levels but increased (P < 0.05) serum alanine aminotransferase activity, as well as caused (P < 0.05) intestinal morphology impairment and inflammation. Supplemental GOD could replace CS to reverse (P < 0.05) the above changes and tended to increase (P = 0.099) average daily gain during ETEC challenge. Besides, GOD addition reversed ETEC-induced losses (P < 0.05) in several beneficial bacteria (e.g. Lactobacillus salivarius) along with increases (P < 0.05) in certain harmful bacteria (e.g. Enterobacteriaceae and Escherichia/Shigella). Functional prediction of gut microbiota revealed that ETEC-induced upregulations (P < 0.05) of certain pathogenicity-related pathways (e.g. bacterial invasion of epithelial cells and shigellosis) were blocked by GOD addition, which also normalized the observed downregulations (P < 0.05) of bacterial pathways related to the metabolism of sugars, functional amino acids, nucleobases and bile acids in challenged piglets. Collectively, GOD could be used as a potential antibiotic alternative to improve growth and serum parameters, as well as attenuate clinical symptoms and intestinal disruption in ETEC-challenged piglets, which could be associated with its ability to mitigate gut microbiota dysbiosis. Our findings provided an evidence for the usage of GOD as an approach to restrict ETEC infection in pigs.